Investigation of magnesium phosphate cement on river dredged sludge with varying humic acid content and solidification mechanism - Xiaoyi Yuan; Lei Peng; Bing Chen (Journal of Rock Mechanics and Geotechnical Engineering)
This paper investigated the use of magnesium phosphate cement (MPC) for solidifying sludge with different humic acid (HA) content (ranging from 0 to 4.5%) and explored the solidification mechanism. Fluidity, setting time, unconfined compressive strength (UCS), the strength formation mechanism, and the spontaneous imbibition process of solidified sludge (SS) were studied. The results indicate that MPC can be used as a low-alkalinity curing agent. As the HA content increases, fluidity and setting time also increase, while hydration temperature and strength decrease. Additionally, the failure mode of SS transitions from brittleness to ductility. The strength of SS is composed of the cementation strength provided by MPC hydration products, matric suction, osmotic suction, and the structural strength of the sludge. MPC reduces the structural strength caused by the shrinkage of pure sludge under the action of matric suction, but the incorporation of MPC significantly improved the strength when the sludge is eroded by water. X-ray diffraction (XRD) and scanning electron microscopy (SEM) show that the sludge and MPC can form a dense solid body, forming various hydration products, and synergistically improve the mechanical properties of the sludge.